Occupational burnout among obstetrics and gynaecology healthcare professionals in a public hospital in Islamabad, Pakistan - Kashif, Sabin; Foong Chan Choong (Journal of the Pakistan Medical Association, 2023)
Objective: To assess burnout by the extent of exhaustion and disengagement, and to compare the two elements among obstetrics and gynaecology healthcare professionals. Method: The cross-sectional study was conducted at the Federal Government Polyclinic Hospital, Islamabad, Pakistan, in July and August, 2020 during the coronavirus disease-2019 pandemic, and comprised healthcare professionals from the obstetrics and gynaecology department. Data was collected online using the 25-item Oldenburg Burnout Inventory. Data was analysed using SPSS 26. Results: Of the 142 individuals approached, 102(71.83%) responded; 55(53.92%) doctors, 43(42.15%) nurses and 4(3.92%) operation theatre technicians. Overall, there were 98(96.1%) females, and 67(65.7%) married subjects. Mean exhaustion score was 2.53+0.54 and disengagement score was 2.14+0.57. Burnout was found in 40(39.2%) participants, 83(81.4%) were exhausted, 44(43.1%) were disengaged, and 4(3.1%) were disengaged but not exhausted. Participants aged >50 years were significantly more exhausted and disengaged than the younger ones (p<0.05). Those with work hours >60 per week were significantly more exhausted and disengaged than the rest (p<0.05). Conclusion: Healthcare professionals in obstetrics and gynaecology teams showed considerably high burnout levels during the coronavirus disease-2019pandemic in Pakistan. Key Words: Burnout, Caregiver exhaustion, Healthcare, Professional, Psychological.